Development of Formal Models of Computer Aided Formative Assessment to Help Learning The Dynamics of Rotation - Bagus, Baden (Universitas Islam Negeri Antasari Banjarmasin, South Kalimantan, Indonesia, 2016)
The research objective is to produce a product that is a model of computer aided formal formative assessment on the rotational dynamics of matter, as well as measure the feasibility of a formal model of computer-aided formative assessment through the validation test. This study uses research design and development. The instrument used in the form of a questionnaire for the assessment validator and test the quality of products by users in limited testing. Validation activities include the validation of product development and validation of multiple choice questions as components of the product. Validation carried out by two lecturers and two teachers. Limited trial conducted on 10 students of class XI SMAN 1 Lawang. Type of research data includes quantitative data such as ratings and feedback validator students based on Likert scale, as well as qualitative data in the form of comments and suggestions provided by the validator. The results of the quantitative data analysis showed that the resulting product included in either category so that it does not require a significant revision. Based on qualitative data, the product has been revised based on the comments and suggestions validator. Products produced already is feasible but still requires further research and development, and trials are repeated so that more can be used in the rotational dynamics of learning materials.